Prescription opioid dispensing in Canada: an update on recent developments to 2018 - Jones, Wayne (J Pharm Policy Pract, 2020)
Canada has been home to comparatively extreme developments in prescription opioid (PO) availability and related harms (e.g. morbidity, mortality) post-2000. Following persistent pan-Canadian increases in PO use, select control measures were implemented and PO dispensing levels—while only inconsistently by province—inverted, and began to plateau or decrease post-2012. We examined annual PO dispensing levels in Canada up until 2018, based on representative prescription sample data from community-based retail pharmacies. Annual prescription-based dispensing data were converted into defined daily doses/1000 population/day by province, and mainly categorized into ‘weak’ and ‘strong’ opioids. All provinces indicated decreasing trends in strong PO levels in most recent years, yet with inter-provincial differences of up to one magnitude in 2018; in about half the provinces, dispensing fell to below-2005 levels. British Columbia had the largest decline in strong PO dispensing from its peak rate (− 48.5%) in 2011. Weak opioid dispensing trends remained more inconsistent and bifurcated across Canada. The distinct effects of individual—including many provincially initiated and governed—PO control measures urgently need to be evaluated. In the meantime, recent reductions in general PO availability across Canada appear to have contributed to shortages in opioid supply for existent, sizable (including non-medical) user populations and may have contributed to recent marked increases in illicit opioid use and harms (including rising deaths).